Factores clínico individuales y ambientales asociados a las infecciones respiratorias agudas en menores de 5 años en el Hospital Regional de Loreto 2021 - Ríos Pinedo, Martha Luz (2023)
The objective was to determine the association between individual and environmental clinical factors and acute respiratory infections in children under 5 years of age at the Regional Hospital of Loreto. The method was quantitative with a descriptive correlational design. The sample consisted of 80 medical records of children under five years of age who were diagnosed with acute respiratory infections. The technique used was documentary review and the instruments were the Individual and Environmental Clinical Factors Data Sheet and the Acute Respiratory Infection Diagnostic Data Sheet for children under 5 years of age. For information processing, the SPSS version 24 computational statistical package was used. The results obtained were: 57.8% (47) were between 1 and 11 months and 29 days old, 55% (44) were men, 75% (60) had less than 7 days of illness before reaching the emergency room, 55% (44) required oxygen therapy (41) had 1 to 2 hours to start treatment, 71.3% (57) had less than 7 days of hospital stay, 91.3% (73) had recovered discharge status, 48.8% (39) lived in rural areas, 61.3% (49) had houses with rustic material, 98, 8% (79) had access to drinking water, 76.2% (61) had pneumonia. In conclusion, an association was demonstrated between the diagnosis of Acute Respiratory Infection and: age (p_value = 0.026), sex (p_value = 0.018), time of illness before reaching the emergency room (p_value = 0.035), the requirement of Oxygen therapy (p_value = 0.043), endotracheal intubation/mechanical ventilation (p_value = 0.000) and antibiotic therapy (p_value = 0.026), length of hospital stay (p_value = 0.023), discharge condition (p_value = 0.000), area of residence (p-value = 0.030), construction material (p-value = 0.003), access to basic services (electricity (pvalue = 0.013) and drainage (p_value = 0.005)). Likewise, no association was found with: the requirement of other special procedures (p_value = 0.277), the start time of treatment (p_value = 0.339) and access to water (p_value =0.854).